Preparation and characterisation of gels based on sucrose modified with glycidyl methacrylate - Ferreira, L. (2000)
Sugar-based hydrogels were prepared by non-selective modification of sucrose with the introduction of vinyl groups. Sucrose was reacted with glycidyl methacrylate (1:1 molar ratio) in DMSO and in the presence of 4-(N,N-dimethylamino)pyridine (4-DMAP) as catalyst. The structure of the product (SucMA) was established using 1H NMR, 1H DQF-COSY NMR and 13C NMR analysis. Gels were prepared by copolymerisation of hydroxyethyl methacrylate (HEMA) and SucMA in a 70:30 ethylene glycol/water mixed solvent using ammonium persulphate/sodium methabisulphite pair as initiating system. The swelling behaviour of these gels was evaluated as a function of crosslinker content, copolymer composition, pH and ionic strength. In addition, the diffusional behaviour of sodium salycilate (SSA) from these gels and poly(HEMA) gels is also reported.